Understanding Professional Care from the Viewpoint of Care Receivers and Care Givers - The Necessity of a Special Care Rationality - Margrit Brückner (Social Work and Society)
Aim of the paper is to analyze, which form of support in professional care situations is wanted and needed by care receivers, also looking into wishes and needs of care givers. This gives a chance of understanding what is required in a subject oriented care process taking long lasting care necessities in different fields of social work and nursing as an example, based on a qualitative empirical research project in Germany. The various dimensions of care concerning activities, hopes and structural frames will be discussed as part of a gender theoretical approach. Taking the viewpoints of care receivers and care givers into consideration four central dimensions of care in professional contexts can be shown: the institutional frame, capability of action including relationship building, ethical norms and self care. The results of this analysis are understood as a proof of the relevance of a care term on the basis of"care rationality" (Kari Waerness).